The effectiveness of a 12-week sport nutrition education intervention on female volleyball players performance - Bharathi Palani; Yeddanapalli Chinniah Louis Raj; Yuliya Kalmykova; Swamynathan Sanjaykumar; Svitlana Korsun (Фізична реабілітація та рекреаційно-оздоровчі технології)
Purpose: This study aimed to evaluate the effectiveness of a 12-week sport nutrition education intervention (SNEI) on female volleyball players aged 18 to 25 in Tamil Nadu, India, with a focus on improving nutritional knowledge, dietary habits, body composition, and athletic performance.